Regulation of VEGF receptors by Rb and E2F1: Role of acetylation - Pillai, Smitha (2010)
E2F transcription factors regulate a variety of cellular processes but their role in angiogenesis is not clear. We find that many genes involved in angiogenesis like FLT-1, KDR and angiopoietin 2 have potential E2F1 binding sites in their promoter. ChIP assays showed that E2F1 can associate with these promoters and the recruitment of E2F1 was enhanced upon VEGF stimulation with concomitant dissociation of Rb leading to the transcriptional activation of these promoters. Transient transfection experiments showed that these promoters were induced by E2F1 and repressed by Rb while depletion of E2F1 decreased their expression. The increased binding of E2F1 to these promoters upon VEGF stimulation correlated with acetylation of histones and E2F1; this required VEGFR function, as seen in ChIP-re-ChIP experiments. This suggests the existence of a positive feedback loop regulating E2F1 acetylation and VEGFR expression. Acetylation associated with VEGF signaling appears to be predominantly mediated by PCAF and depletion of histone acetyl transferases disrupted the formation of angiogenic tubules. These results suggest a novel role for E2F1 and acetylation in the angiogenic process.